/
/
/
Then factor the resulting perfect square trinomial
Not my Question
Flag Content

# Question : Then factor the resulting perfect square trinomial : 2145137

Complete the square for the binomial. Then factor the resulting perfect square trinomial.

41) x2 + (4/7)x

A) x2 + (4/7)x + (4/7) = (x + (2/7))2

B) x2 + (4/7)x + (4/49) = (x + (2/7))2

C) x2 + (4/7)x + (2/49) = (x + (2/7))2

D) x2 + (4/7)x + (8/49) = (x + (4/7))2

42) x2 - x

A) x2 - x + 1 = (x - 2)2

B) x2 - x + (1/2) = (x - 1)2

C) x2 - x + (1/4) = (x - (1/2))2

D) x2 - x + (1/2) = (x - (1/4))2

Solve the quadratic equation by completing the square.

43) x2 + 14x + 33 = 0

A) {-11, -3}

B) {11, -3}

C) {-11, 44}

D) {3, 11}

44) x2 + 10x = -21

A) {-7, -3}

B) {±√(21)}

C) {28, -7}

D) {3, 7}

45) x2 + 10x = -11

A) {-5 ± √(14)}

B) {-5 ± √(11)}

C) {5 ± √(14)}

D) {-10 ± √(11)}

46) x2 + 3x - 9 = 0

A) {(-3 ± √(5)/2)}

B) {(-3 ± 3√(5)/2)}

C) {-3 ± 3√(5)}

D) {(3 ± 3√(5)/2)}

47) x2 + 8x - 7 = 0

A) {-4 ± 2√(23)}

B) {4 ± √(23)}

C) {-4 ± √(23)}

D) {-1 ± √(23)}

48) x2 - 8x = 3

A) {4 ± √(3)}

B) {8 ± √(67)}

C) {-4 ± √(19)}

D) {4 ± √(19)}

49) x2 + 4x = 9

A) {-1 ± √(13)}

B) {-2 ± √(13)}

C) {2 ± √(13)}

D) {-2 ± 2√(13)}

50) x2 = -8x + 7

A) {-4 ± √(23)}

B) {4 ± √(23)}

C) {-4 ± 2√(23)}

D) {-1 ± √(23)}

## Solution 5 (1 Ratings )

Solved
Algebra 1 Week Ago 9 Views